RHEUMATISM IN CHILDREN (The Role of Exact Sciences in the Era of Modern Development, 2024)
Rheumatism is a systemic inflammation of all tissues in the body, mainly localized in the pericardium. Especially the heart, joint and subcutaneous connective tissue in the body are prone to disease. Rheumatism can be caused by simple angina, which is common among people. Tonsillitis itself is acute, accompanied by fever, headache, and inflammation in rheumatic fever leads to chronic heart valve damage, which can lead to disability or death many years after the acute illness. can bring.